Calendar of holding sports competitions as a source in study of features of development of domestic sport in the 30s of the xxth century - Anastasia Bondar; Nataliia Saltan; Oleksandr Saltan (Kharkiv State Academy of Physical Culture, 2015)
Purpose: based on the analysis of a number of archive documents made an attempt to investigate the dynamics of development of Olympic and non-Olympic sports in the first decades of the Soviet period of the Ukrainian history. Materials and Methods: the analysis and generalization of sources on the subject. Results: the features of the development of sports industry of the USSR in the 30-ies of 20th century are analyzed. Conclusion: it is proved, that the development of the sports field was caused by primarily political factors; equal attention was paid to Olympic and non-Olympic kinds of sports